THE DYNAMIC DEVELOPMENT ON INDONESIA’S ATTITUDE TOWARD INTERNATIONAL LAW - Agusman, Damos Dumoli (Indonesian Journal of International Law, 2015)
The paper discusses the relation between international law and domestic law in the context of Indonesia. The paper examines Indonesia’s viewpoints on international law by analysing the various stages in Indonesia’s history from its independence through the present times. The attitude of Indonesia toward international law since its independence as a sovereign state has been changing progressively, from hostility to friendly. berita terupdate saat ini in Indonesia, therefore, should shape its domestic legal system in such manner where international law acquires a proper legal status under it. It appears that the Indonesian legal system is not yet being developed into such direction.